Optimal break structures and cooling strategies to mitigate heat stress during a Rugby League match simulation. Issue 8 (August 2021) - Graham, Connor; Lynch, Grant P.; English, Timothy; Hospers, Lily; Jay, Ollie
Abstract: Objectives: To examine, 1) optimal structure of break periods to mitigate physiological heat strain during rugby league play ( Stage 1 ); and ii) effectiveness of three different cooling strategies applied during breaks ( Stage 2 ). Design: Counter-balanced crossover design. Methods: In 37 °C, 50% RH, 11 males completed six simulated 80-min (two 40-min halves) rugby league matches on a treadmill with different break structures: regular game (RG) (12-min halftime), 1-min or 3-min "quarter-time" breaks halfway through each half with a 12-min halftime break (R1C and R3C), a 20-min halftime break (EH), or 1-min or 3-min quarter-time breaks with a 20-min halftime break (E1C and E3C) [ Stage 1 ]. Nine participants completed Stage 2, which assessed the application of either ice towels (ICE), an electric fan (FAN) or a misting fan (MST) during breaks in the E3C protocol which, in Stage 1, prevailed as the optimal break structure. Results: Stage 1 : Irrespective of quarter-time break duration, reductions in rectal temperature (−0.24 °C ± 0.24) and heart rate (−61 ± 10 bpm) during the halftime break were greater with a 20-min compared to a 12-min break (−0.08 ± 0.13 °C, p = 0.005; −55 ± −9 bpm, p = 0.021). Stage 2 : End-game rises in rectal temperature were smaller ( p < 0.006) in MST (1.41 ± 0.22 °C), FAN (1.55 ± 0.36 °C) and ICE (1.60 ± 0.21 °C) than in CON (1.80 ± 0.39 °C). The end-halftime heart rate was lower ( p < 0.001) in ICE (89 ± 13 bpm), MST (90 ± 10 bpm) and FAN (92 ± 13 bpm) than in CON (99 ± 18 bpm). Conclusions: Combining an extended halftime period and quarter-time breaks with MST application is the optimal cooling strategy for rugby league players in hot, humid conditions.